Assessment of fungal contamination in fish feed from the Lake Victoria Basin, Uganda - Namulawa, V.T.; Mutiga, Samuel K.; Musimbi, F.; Akello, S.; Ng'ang'a, Fredrick M.; Kago, Leah; Kyallo, Martina M.; Harvey, Jagger J.W.; Ghimire, Sita R. (MDPI, 2020)
The emergence of commercial fish farming has stimulated the establishment of fish feed factories in Uganda. However, no information is available on the safety of the feed, mainly due to lack of mycotoxin testing facilities and weak regulatory systems. A study was carried out to examine fungal colonization and mycotoxin contamination in fish feed samples (n = 147) of different types collected from nine fish farms (n = 81) and seven fish feed factories (n = 66) in the Lake Victoria Basin (LVB). Fungi were isolated in potato dextrose agar, grouped into morphotypes and representative isolates from each morphotype were identified based on the internal transcribed spacer (ITS) region of ribosomal DNA sequences. Aflatoxin B1 (AFB1) and total fumonisin (combinations of B1, B2 and B3; hereinafter named fumonisin) levels in feed samples were determined by enzyme-linked immunosorbent assay (ELISA). A wide range of fungi, including toxigenic Aspergillus flavus and Fusarium verticillioides, were isolated from the fish feed samples. AFB1 was detected in 48% of the factory samples and in 63% of the farm samples, with toxin levels <40 and >400 µg/kg, respectively. Similarly, 31% of the factory samples and 29% of the farm samples had fumonisin contamination ranging between 0.1 and 4.06 mg/kg. Pellets and powder had higher mycotoxin contamination compared to other commercially available fish feed types. This study shows AFB1 as a potential fish feed safety issue in the LVB and suggests a need for more research on mycotoxin residues in fish fillets.